Prospective associations between early childhood intimate partner violence exposure and middle childhood internalizing and externalizing psychopathology - Lee, Amy Hyoeun (Child maltreatment, 2023)
Co-occurring adversities are common for young children with child protective services (CPS) involvement, with high rates of intimate partner violence (IPV) exposure in this population. Despite extensive research linking childhood IPV exposure to later psychopathology, fewer studies have examined the prospective associations between IPV exposure and psychopathology using a dimensional approach. Here, we conducted secondary analyses of data from a randomized controlled trial of a parenting intervention for CPS-involved children, examining the associations between early childhood IPV exposure (i.e., threat), co-occurring deprivation, and middle childhood internalizing and externalizing symptoms. Adversity variables were coded from data collected when children were infants (N = 249, Mage = 7.97 months) through 48-month assessments; internalizing and externalizing psychopathology were modeled as latent variables reflecting the mean of data from yearly assessments between ages 8 to 10. Results of our structural equation model demonstrated that, accounting for the effects of co-occurring deprivation, IPV exposure was significantly associated with both internalizing, ? = .38, p = .001, and externalizing, ? = .26, p = .019, symptoms. Results suggest links between early childhood IPV exposure (i.e., threat) and later psychopathology. Findings support screening and intervention efforts to mitigate the developmental sequelae of IPV exposure among CPS-involved children.